Hybrid energy storage systems for power networks - Yeang, Zhong Wei. (2012)
Renewable energy sources, such as solar, wind and hydraulic energies have been used for many centuries and their applications continued throughout history and until the industrial revolution. By which time, due to the low price of fossil fuels such as oil, coal and natural gas, the renewable energies were abandoned. Energy consumption rate is expected to increase in the foreseeable future due to the population growth and industrialization.